NAFKAH ANAK PASCA TERJADINYA IKRAR TALAK DALAM PERSPEKTIF HUKUM ISLAM (Studi Terhadap Tanggungjawab Ayah dalam Putusan Pengadilan Agama Bengkulu Perkara Nomor: 479/Pdt.G/2020/PA.Bn) - Nengsih, Yulia (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2021)
Abstract: This research raises the problem of what the panel of judges considered in the decision of the case Number 479 / Pdt.G / 2020 / PA.Bn on the father’s responsibility after the divorce pledge at the Bengkulu Religious Court Class IA in the perspective of Islamic law and how the father’s obligation to support the child after pledge of divorce in the case decision Number: 479 / Pdt.G / 2020 / PA-Bn at the Bengkulu Class IA Religious Court. This research uses the type of field research (field) and library research (literature), with a statutory approach, a case approach and a conceptual approach. To collect data, the documentary method was used which was obtained from the Bengkulu religious court’s decision on the case Number: 479 / Pdt.G / 2020 / PA.Bn and literature review refers to books that discuss issues that correspond to the problem. Then after the data obtained were analyzed descriptively normative. The research results show that: 1) The judges’ consideration that the father’s responsibility after the divorce vow to the child after the divorce is more burdened on the father and a mother is not obliged to provide for her child, whether there is a husband on her side or not. Whether the woman is rich or poor, a woman only has an obligation to provide for her parents and the slave she has. This is confirmed by the syafi’i, Hanafi and Hambali schools, if the father is unable to provide for the child, then the closest relatives can take over the role of the father to provide a living. 2) The obligation of the father to support the child after the divorce pledge in the decision of the case Number: 479 / Pdt.G / 2020 / PA-Bn at the Bengkulu Religious Court, namely punishing the Petitioner (father) to provide for the child outside the cost of education and health. If the Petitioner’s father renounces and does not fulfill his obligations as stated in the dictum of four orders of the Respondent’s decision, the Respondent may apply for the execution of the payment of child support to the Religious Court to force the male parent (father) to provide a living cost. Keywords: Child’s Livelihood, Father’s Responsibility, Islamic Law Abstrak: Penelitian ini mengangkat permasalahan apa pertimbangan majelis hakim dalam putusan perkara Nomor 479/ Pdt.G/2020/PA.Bn terhadap tanggung jawab ayah setelah ikrar talak di Pengadilan Agama Bengkulu Kelas IA dalam perspektif hukum Islam dan bagaimana kewajiban ayah terhadap nafkah anak pasca ikrar talak pada putusan perkara Nomor: 479/ Pdt.G/2020/PA-Bn di Pengadilan Agama Bengkulu Kelas IA. Penelitian ini menggunakan jenis penelitian field research (lapangan) dan library research (kepustakaan), dengan pendekatan undang-undang, pendekatan kasus dan pendekatan konseptual. Untuk mengumpulkan data digunakan metode dokumenter yang didapat dari putusan pengadilan agama Bengkulu pada perkara Nomor : 479/Pdt.G/2020/PA.Bn dan tinjauan pustaka merujuk pada pada buku-buku yang membicarakan masalah yang sesuai dengan permasalahan. Kemudian setelah data didapat dianalisis secara deskriptif normatif. Dari hasil penelitian menunjukan bahwa: 1) Pertimbangan majelis hakim bahwa tanggung jawab ayah setelah ikrar talak terhadap anak pasca perceraian yaitu lebih dibebankan kepada ayah dan seorang ibu tidak wajib memberikan nafkah kepada anaknya, baik itu ada suami di sisinya maupun tidak ada. Baik itu perempuannya kaya maupun miskin, seorang perempuan hanya punya kewajiban memberi nafkah kepada kedua orang tua dan budak yang dimilikinya. Hal ini ini dipertegas oleh mazhab syafi’i, Hanafi dan Hambali, apabila ayah tidak mampu menafkahi anak, maka kerabat terdekat bisa mengambil alih peran ayah untuk memberikan nafkah. 2) Kewajiban ayah terhadap nafkah anak pasca ikrar talak pada putusan perkara Nomor: 479/Pdt.G/2020/PA-Bn di Pengadilan Agama Bengkulu, yaitu menghukum Pemohon (ayah) untuk memberi nafkah anak diluar biaya pendidikan dan kesehatan. Jika ayah (Pemohon) ingkar dan tidak memenuhi kewajibannya sebagaimana dalam dictum empat amar putusan Termohon dapat mengajukan permohonan eksekusi pembayaran biaya nafkah anak ke Pengadilan Agama untuk memaksa orang tua laki-laki (ayah) tersebut untuk memberikan biaya nafkah. Kata Kunci: Nafkah Anak, Tanggungjawab Ayah, Hukum Islam